KEMISKINAN DALAM PERSPEKTIF AL-QUR’AN - Habibah, Nuraini (IAINU Kebumen Prodi IAT, 2023)
Poverty is a social economic problem throughout the history of mankind. Even in Islam poverty/poverty can lead to disbelief, therefore it needs to get serious treatment from various parties. Islam offers several ways and efforts to alleviate poverty which are broadly divided into three, namely: (1) Self-made efforts; (2) The method pursued by other people/society; (3) The method pursued by the government. By using a qualitative descriptive method, this study tries to explain the concept of poverty and ways of reducing poverty from an Islamic perspective.